Detection of Pesticides in Organic Fruits and Vegetables Using Artificial Intelligence and IOT - Mrs. C. Vijaya Lakshmi,; Nadimpalli Rajasekhar, (International Journal of Scientific Research in Science and Technology, 2024)
The escalating usage of pesticides, steroids, and fertilizers in agriculture poses significant risks to human health. These substances infiltrate the human body through the consumption of contaminated fruits and vegetables. To address these concerns, an effective solution for pesticide analysis in everyday produce is essential. Below is a detailed overview of the issue, supported by data on the adverse impacts on human health and potential solutions for effective pesticide analysis. Through the integration of hardware and software designs, this project endeavors to provide accurate, real-time detection of pesticide levels. Utilizing sensors and Arduino technology, the system aims to deliver comprehensive insights into pesticide presence. Embedded C Program facilitates the establishment of a threshold value for pesticide concentration deemed safe for consumption by both humans and animals. Any fruit registering pesticide levels exceeding this threshold is flagged as potentially hazardous, highlighting the importance of vigilant monitoring in ensuring food safety. Efforts to address the pervasive issue of pesticide contamination in agricultural produce have led to the development of innovative solutions. This project leverages sensor technology and Arduino platforms to enable precise detection of pesticide residues in fruits and vegetables. By establishing a predefined threshold for acceptable pesticide levels, the system provides valuable guidance for consumers concerned about food safety. Through real-time analysis and embedded programming, it offers a proactive approach to identifying produce that may pose health risks due to elevated pesticide concentrations. This integration of hardware and software underscores the potential of technology-driven solutions in safeguarding public health and promoting informed decision-making regarding food consumption.
Keywords: IOT; Arduino Mega; GSM; PH Sensor; Gas Sensor; NODE MCU